ChemInform Abstract: On the Control Parameters of the Quasi‐One Dimensional Superconductivity in Sc3CoC4. Issue 2 (14th January 2014) - Eickerling, Georg; et al., et al.
Abstract A detailed analysis of structural, electronic, and vibrational properties of the low‐temperature phase of Sc3CoC4, which is one of a few well‐documented quasi one‐dimensional superconductors, is presented.